The Integration of digital payments within the Asia-Pacific region in the age of artificial intelligence - Yensen Ni,; Mu-Hsiang Yu, (Eximia, 2025)
The widespread use of the internet and AI-powered mobile phones has contributed to the new integration trend of development of digital payments in the Asia-Pacific region. Despite the importance of digital payments in accelerating regional integration, a lack of research analysis of regional integration in the age of Artificial Intelligence (AI) could be hindered by national security concerns. The study begins by outlining the theory of economic integration and AI Executive Order in the U.S.A, followed by analysis of the limitations in the bilateral or multi-agreements for improving the connectivity of cross-border digital payments in the region. The findings indicate that the regional integration of digital payments still faces major bottlenecks, although AI is regarded as a transformative force in facilitating cross-border digital payments. The originality of this study lies in interdisciplinary approach, combining digital payments innovation with economic integration theory and policy analysis to support valuable insights for policymakers in the field of management, particularly in enhancing regulatory harmonization and governance of digital payments in the context of the AI era.